2019
DOI: 10.1111/jfd.13000
|View full text |Cite
|
Sign up to set email alerts
|

Potential vector species of carp edema virus (CEV)

Abstract: During a PCR‐based CEV survey in Poland in 2015–2017, the virus was detected in many farms both in clinical and asymptomatic cases and in common as well as in koi carp (Cyprinus carpio). In order to evaluate the potential carrier role of fish species that share the same habitats with carp, an experimental trial was performed. Investigations carried out on specimens of bleak (Alburnus alburnus), crucian carp (Carassius carassius), European perch (Perca fluviatilis), Prussian carp (Carassius gibelio), roach (Rut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 10 publications
1
24
0
1
Order By: Relevance
“…The overlap between the water thermal conditions optimal for the spawning of round goby and those conducive to the replication cycle of KHV, transmitted by this fish species, creates a very dangerous phenomenon. Matras et al (19) confirmed the presence of the carp oedema virus in tench, crucian carp, Prussian carp, roach, bleak, and European perch. KHV was detected in 18 species besides the carp (15).…”
Section: Discussionmentioning
confidence: 92%
“…The overlap between the water thermal conditions optimal for the spawning of round goby and those conducive to the replication cycle of KHV, transmitted by this fish species, creates a very dangerous phenomenon. Matras et al (19) confirmed the presence of the carp oedema virus in tench, crucian carp, Prussian carp, roach, bleak, and European perch. KHV was detected in 18 species besides the carp (15).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Matras, Stachnik, Borzym, Maj‐Paluch, and Reichert (2019) postulated that heterologous species such as bleak, crucian carp, Prussian carp, European perch, roach and tench may play a role as vectors in CEV epidemiology. They found a specimen of the mentioned warm‐water fish species to be CEV‐positive 72 hr after co‐habitation with CEV‐infected common carp.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis revealed that mortalities at the carp farms in cases one and four were caused by CEV sharing the same nucleo- cohabitated with infected carp (Matras, Stachnik, Borzym, Maj-Paluch, & Reichert, 2019). In such cases, despite viral DNA being detected in the gills (gills and skin in roach), the infected fish failed to develop clinical CEVD and no mortalities were observed (Matras et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis revealed that mortalities at the carp farms in cases one and four were caused by CEV sharing the same nucleo- cohabitated with infected carp (Matras, Stachnik, Borzym, Maj-Paluch, & Reichert, 2019). In such cases, despite viral DNA being detected in the gills (gills and skin in roach), the infected fish failed to develop clinical CEVD and no mortalities were observed (Matras et al, 2019). CEV genome fragments have also been detected in gill tissue of grass carp (Ctenopharyngodon idella), northern pike (Esox lucius), ruffe (Gymnocephalus cernua), perch and pike-perch (Sander lucioperca) kept together with common carp (Jung-Schroers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%